Targeting Colorectal Cancer Cells with a Functionalised Calix[4]arene Receptor: Biophysical Studies - Angela F Danil de Namor; Nawal Al Hakawati; Sami Y Farhat (Molecules, 2022)
Colorectal cancer (CRC) is a disease which is causing a high degree of mortality around the world. The present study reports the antiproliferative impact of the thioacetamide calix[4]arene, CAII receptor on a highly differentiated Caco-2 cell line. This statement is corroborated by the MTT assay results which revealed a reduction in the cell viability with an IC50 value of 19.02 ± 0.04 µM. Microscopic results indicated that at the starting amount of 10 µM of CAII, a decrease in cells confluency can already be observed in addition to changes in cells morphology. Cell metabolic pathway changes were also investigated. 1H NMR findings showed downregulation in lactate, pyruvate, phosphocholine, lipids, and hydroxybutyrate with the upregulation of succinate, indicating a decline in the cells proliferation. Some biochemical alterations in the cells as a result of the CAII treatment were found by Raman spectroscopy.